Hubungan Higiene Pengguna Air Sungai Deli Dengan Keluhan Kesehatan Kulit Dan Tindakan Pencemaran Sungai Di Kelurahan Hamdan Kecamatan Medan Maimun Kota Medan Tahun 2013 - leo waldi purba; evi naria; indra chahaya (Lingkungan dan Kesehatan Kerja, 2014)
Relationships Hygiene Deli River Water Users With Skin Health Complaints and Actions River Pollution In the Hamdan Village District of Medan Maimun in 2013. The people who using river as clean water can cause health complaints those are itching. The purpose of this study was to investigate relationships between hygiene Deli River water users with skin health complaints and the description of river pollution action in the Hamdan Village District of Medan Maimun.This research is an analytical survey with cross sectional research design, to know how the relationships between with skin health complaints of river users and to describe river pollution action. The population of this study are all housewives or the people aged 16 years or over represent that use river water for bathing, washing and toilet which amounted to 52 people with total sampling. The data used are primary data and secondary data. The data was analyzed using chi square test. The results showed that the largest percentage of water users is based on the age at age 16-25 years, the largest percentage based on the level of education is primary school graduation the largest percentage based on the type of work are housewife, and most income is Rp. 800.000-Rp 1.500.000. River water users have not good hygien. Water users have experience health complaints of skin with the largest percentage of symptoms are itching. There was relation between hygiene with health complaints of skin (p = 0.025). Most of the river water users perform actions littering the river pollution into the river each day. Local authorities should provide facilities and infrastructure trash in the river and the construction of water supply and disposal of water for people to use a large enough clean water, not defecating in the river and not throw garbage in the river. Keywords: pollution action, hygiene, health complaints